Liturgiateoloogia ja liturgiauuendus - Kotila, Heiki (Usuteaduslik Ajakiri, 2007)
Heikki Kotila, Liturgical Theology and the Renewal of Liturgy The aim of this article is to explore the relationship between the worship renewal of the Evangelical Lutheran Church in Finland and the study of liturgical theology. The article first describes the various attempts at liturgical renewal in Finland. The new liturgical books - Service Book, Lectionary 2000 and The Book of Occasional Services 2004 for the Evangelical Luther Church in Finland - are the final result of this work. The process of renewal can be understood in the context of the ecumenical liturgical movement. For instance, The Evangelical Lutheran Church in Finland has used texts from the service books of other churches, like service books prepared for the use of the Church of Sweden and the Evangelical Lutheran Church in America. The nature and development of liturgical theology are then discussed. The author states that practical liturgical changes are the impetus for the study of liturgical theology. The purpose of liturgical theology is not to study the worship practices as a closed system, but rather to explore the relationship between the worshipping community and the society around the church.